2006
DOI: 10.3354/meps325015
|View full text |Cite
|
Sign up to set email alerts
|

Mesocosm study of particle dynamics and control of particle-associated bacteria by flagellate grazing

Abstract: The goal of this study was to attain an integrated understanding of the dynamics of attached microbial communities in nature as governed by the component processes of particle formation, colonization, detachment, growth and interspecific interactions among the microbes. The study was conducted in mesocosms in a Danish fjord over a 2 wk period in April to May 2005. Despite nutrient additions, chlorophyll and particle concentrations were low and no distinct phytoplankton blooms were observed. Particle volume con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
(64 reference statements)
1
8
0
Order By: Relevance
“…Marine and freshwater detritus attract not only bacteria but also bacterivorous protozoans (Simon et al 2002). In a recent mesocosm study on particle-associated bacteria, Tang et al (2006a) showed that strong grazing pressure from bacterivorous flagellates kept the attached bacterial population at a low level. In a preliminary study, we observed ciliates swimming around decomposing copepod carcasses collected from Lake Dagow (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marine and freshwater detritus attract not only bacteria but also bacterivorous protozoans (Simon et al 2002). In a recent mesocosm study on particle-associated bacteria, Tang et al (2006a) showed that strong grazing pressure from bacterivorous flagellates kept the attached bacterial population at a low level. In a preliminary study, we observed ciliates swimming around decomposing copepod carcasses collected from Lake Dagow (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Because rates of bacterial solubilization are often higher than those of uptake, dissolved organic matter would leak out of the detritus and benefit bacteria even in the surrounding water (Grossart & Simon 1998, Kiørboe et al 2001. Accumulation of bacteria due to attachment and growth would also transform the detritus into hotspots for bacterivory (Caron 1987, Kiørboe et al 2004, Tang et al 2006a) and genetic material exchange (Turley & Mackie 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Although aggregates represent a source of nutrients for marine snow bacteria, they are also risky environments where bacteria could be exposed to high grazing pressure (Caron 1987. In a recent mesocosm study, Tang et al (2006) showed that strong grazing pressure from flagellated protozoa could limit the residence time of bacteria on aggregate surfaces (calculated as the steady-state abundance of bacteria divided by the colonization rate) to 21 min or less. The duration of attachment to aggregates may be a trade-off between the risk of predation and the need for nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Fecal enrichment may have occurred through a combination of continued microbial colonization, growth, mineralization, and uptake of dissolved inorganic nitrogen from the surrounding water column. Protozoans, such as flagellates and ciliates, colonize feces soon after bacteria, and their grazing can stimulate bacterial population growth, hydrolysis, and mineralization (Johannes 1965, Jacobsen & Azam 1984, Pomeroy et al 1984, Biddanda & Pomeroy 1988, Tang et al 2006. Protozoans also remineralize DOM released by particle-associated bacteria, contributing to the enrichment of fecal aggregates (Pomeroy et al 1984, Biddanda & Pomeroy 1988, Grossart & Ploug 2001.…”
Section: Discussionmentioning
confidence: 99%
“…High rates of detachment by the particle-associated bacteria and uptake of DOM by free-living bacteria also contribute to the loss of organic matter from fecal aggregates (pellet and attached microbes) (Jacobsen & Azam 1984, Peduzzi & Herndl 1986, Kiør-boe et al 2003, Tang et al 2006. We observed the greatest decrease in fecal mass and organic carbon and nitrogen content within 3 d, which is consistent with the temporal peak in microbial activity (1 to 4 d post egestion) for feces of various aquatic animals (Jacobsen & Azam 1984, Peduzzi & Herndl 1986, Yoon et al 1996, Kiørboe et al 2003, Tang et al 2006. The rapid dissolution of DOM and bacterial hydrolysis of POM from the large quantity of feces egested (approx.…”
Section: Discussionmentioning
confidence: 99%